Fatigue Life Enhancement of Three Point Hitch System Brackets in the Garden Series Tractors - İbrahim Savaş Dalmış; Olcay Tezcan; Sait Özmen Eruslu (Journal of Agricultural Sciences)
The main objective of this research was to enhance the fatigue performance of the brackets found in the three point hitch system used in garden series tractors. This was achieved by using experimental tests and finite element analysis. The manufactured brackets were validated with fatigue rig tests, namely a lifting capacity test, a push-pull test and a liftinglowering test. The lifting capacity test of three point hitch mechanism was established according to ISO 730-1 standards. In addition to the lift capacity test, problems were also experienced with the cylinder clamping brackets during the pushpull tests. The bracket brakeage occurred during the 11,218th test cycle. According to the test results and finite element analysis, the brackets were strengthened at critical damage points. The thickness of the bracket connection surface was increased from 12 mm to 19 mm and the bracket material was changed from GG25 to GG35. The enhanced brackets passed the tests without any breakage